REACTION OF PAROTID GLANDS AND BUCCAL EPITHELIUM IN CHILDREN WITH MALIGNANCIES OF THE ABDOMINAL CAVITY IN THE BACKGROUND RECEIVING CHEMOTHERAPY - Ткаченко, П.І.; Попело, Ю.В.; Білоконь, С.О. (World of Medicine and Biology, 2016)
The paper presents the results of a survey of 21 children aged 7 to 16 years with solid tumors of the abdomen, which took two courses of chemotherapy. The study of the secretory activity of the parotid glands revealed a decrease in the production parotitno secret, and the appearance in zithromax as destroyed, and the preserved forms of peripheral blood cells with a predominance among them of white blood cells with signs of dystrophy gtopo. In smears-perevod obtained from buccal mucosa was determined in a large number of desquamating of buccal epithelium cells with signs of destruction of the nuclei, cell membranes and increased their contamination with microorganisms, the severity of which depended on the duration of carrying out of chemotherapy. These markers can serve as objective criteria for the assessment of tissues and organs of the oral cavity and to determine the effectiveness of preventive measures in children receiving chemotherapy.
Keywords: children; malignant tumor of the parotid gland; buccal cells; chemotherapy; citogramma